Infections Due to Carbapenem-Resistant Bacteria in Patients With Hematologic Malignancies - Lalaoui, Rym; Javelle, Emilie; Bakour, Sofiane; Ubeda, Carles; Rolain, Jean-Marc (Frontiers in Microbiology, 2020)
In developed countries, hematological malignancies (HM) account for 8 to 10% of cancers diagnosed annually and 1/3 of patients with HM (HMP) are expected to die from their disease. The former wide spectrum "magic bullet", imipenem, has been ousted by the emergence of carbapenem resistant (CR) pathogens. In endemic areas, infections with CR-bacteria occur in vulnerable patients, notably in HMP, who suffer from high mortality related to infectious complications. In this work, we reviewed epidemiologic and clinical factors associated with CR-infections in adult HMP, and data on CR-related mortality and antibiotic treatments in this population We found that resistance profile of strains involved in HMP infections, mainly bacteremia, reflect local epidemiology. Significant risk factors for infections with CR-bacteria include sex male, age around 50 years old, acute leukemia, selvage chemotherapy, neutropenia, and digestive colonization by CR-bacteria. Mortality rate is high in HMP infected with CR-Enterobacteriaceae, more particularly in case of acute myeloid leukemia and unresolved neutropenia, due to inappropriate empiric management and delayed administration of targeted antibiotics such as tigecycline, colistin or new associations of active drugs. Thus, we developed an algorithm for clinicians, assessing the incremental risk for CR-bacterial infection occurrence and mortality in febrile HMP, to guide decisions related to empirical therapeutic strategies.